Ecocritical Perspectives on Children's Texts and Cultures Nordic Dialogues (Critical Approaches to Children's Literature, 2018)
This volume presents key contributions to the study of ecocriticism in Nordic children's and YA literary and cultural texts, in dialogue with international classics. It investigates the extent to which texts for children and young adults reflect current environmental concerns. The chapters are grouped into five thematic areas: Ethics and Aesthetics, Landscape, Vegetal, Animal, and Human, and together they explore Nordic representations and a Nordic conception, or feeling, of nature. The textual analyses are complemented with the lived experiences of outdoor learning practices in preschools and schools captured through children's own statements. The volume highlights the growing influence of posthumanist theory and the continuing traces of anthropocentric concerns within contemporary children's literature and culture, and a non-dualistic understanding of nature-culture interaction is reflected in the conceptual tool of the volume: The Nature in Culture Matrix.